TEX/Favorites: Difference between revisions

From Web
Jump to navigation Jump to search
No edit summary
mNo edit summary
 
Line 1: Line 1:
\textstyle \frac{x}{y} \frac{x}{y}
{|
\textstyle \sum_x^n \sum_{x=1}^{n}
|-
\textstyle \prod_x^n \prod^{x=1}_{n}
| <amsmath>\frac{x}{y}</amsmath>
\textstyle \int_a^b \int_{a}^{b} f (x)\,dx
| \frac{x}{y}
\textstyle \frac{\partial x}{\partial y} \frac{\partial x}{\partial y}
|-
\textstyle \sqrt x \sqrt{x}
| <amsmath>\sum_{x=1}^{n}</amsmath>
\textstyle \sqrt[3]{x} \sqrt[3]{x}
| \sum_{x=1}^{n}
\textstyle f(x) f(x)
|-
\lim \lim_{x\to\infty}
| <amsmath>\prod^{x=1}_{n}</amsmath>
***
| \prod^{x=1}_{n}
\sin \sin (x)
|-
\cos \cos (x)
| <amsmath>\int_{a}^{b} f (x)\,dx</amsmath>
\tan \tan (x)
| \int_{a}^{b} f (x)\,dx
\log \log (x)
|-
\ln \ln (x)
| <amsmath>\frac{\partial x}{\partial y}</amsmath>
***
| \frac{\partial x}{\partial y}
\le \le
|-
\ge \ge
| <amsmath>\sqrt{x}</amsmath>
\neq \neq
| \sqrt{x}
\approx \approx
|-
\equiv \equiv
| <amsmath>\sqrt[3]{x}</amsmath>
\propto \propto
| \sqrt[3]{x}
\infty \infty
|-
***
| <amsmath>f(x)</amsmath>
\alpha \alpha
| f(x)
\beta \beta
|-
\gamma \gamma
| <amsmath>\lim_{x\to\infty}</amsmath>
\delta \delta
| \lim_{x\to\infty}
\epsilon \epsilon
|-
\zeta \zeta
| <amsmath>\sin (x)</amsmath>
\eta \eta
| \sin (x)
\theta \theta
|-
\vartheta \vartheta
| <amsmath>\cos (x)</amsmath>
\kappa \kappa
| \cos (x)
\lambda \lambda
|-
\mu \mu
| <amsmath>\tan (x)</amsmath>
\xi \xi
| \tan (x)
\pi \pi
|-
\rho \rho
| <amsmath>\log (x)</amsmath>
\sigma \sigma
| \log (x)
\tau \tau
|-
\phi \phi
| <amsmath>\ln (x)</amsmath>
\varphi \varphi
| \ln (x)
\chi \chi
|-
\psi \psi
| <amsmath>\le</amsmath>
\omega \omega
| \le
***
|-
\Rightarrow \Rightarrow
| <amsmath>\ge</amsmath>
\rightarrow \rightarrow
| \ge
\Leftarrow \Leftarrow
|-
\leftarrow \leftarrow
| <amsmath>\neq</amsmath>
\Leftrightarrow \Leftrightarrow
| \neq
\vec{x} \vec{x}
|-
***
| <amsmath>\approx</amsmath>
( \left(
| \approx
) \right)
|-
[ \left[
| <amsmath>\equiv</amsmath>
] \right]
| \equiv
\{ \left{
|-
\} \right}
| <amsmath>\propto</amsmath>
\textstyle {n \choose k} {n \choose k}
| \propto
***
|-
\Box \Box
| <amsmath>\infty</amsmath>
\forall \forall
| \infty
\exists \exists
|-
\in \in
| <amsmath>\alpha</amsmath>
\not\in \not\in
| \alpha
***
|-
\mbox{Taylor} f(x) = \sum_{k=0}^{\infty } \frac{ f^{k} (a) }{ k! } (x - a)^k
| <amsmath>\beta</amsmath>
\mbox{Euler}^1 e^{i \varphi } := \cos \varphi + i \sin \varphi
| \beta
|-
| <amsmath>\gamma</amsmath>
| \gamma
|-
| <amsmath>\delta</amsmath>
| \delta
|-
| <amsmath>\epsilon</amsmath>
| \epsilon
|-
| <amsmath>\zeta</amsmath>
| \zeta
|-
| <amsmath>\eta</amsmath>
| \eta
|-
| <amsmath>\theta</amsmath>
| \theta
|-
| <amsmath>\vartheta</amsmath>
| \vartheta
|-
| <amsmath>\kappa</amsmath>
| \kappa
|-
| <amsmath>\lambda</amsmath>
| \lambda
|-
| <amsmath>\mu</amsmath>
| \mu
|-
| <amsmath>\xi</amsmath>
| \xi
|-
| <amsmath>\pi</amsmath>
| \pi
|-
| <amsmath>\rho</amsmath>
| \rho
|-
| <amsmath>\sigma</amsmath>
| \sigma
|-
| <amsmath>\tau</amsmath>
| \tau
|-
| <amsmath>\phi</amsmath>
| \phi
|-
| <amsmath>\varphi</amsmath>
| \varphi
|-
| <amsmath>\chi</amsmath>
| \chi
|-
| <amsmath>\psi</amsmath>
| \psi
|-
| <amsmath>\omega</amsmath>
| \omega
|-
| <amsmath>\Rightarrow</amsmath>
| \Rightarrow
|-
| <amsmath>\rightarrow</amsmath>
| \rightarrow
|-
| <amsmath>\Leftarrow</amsmath>
| \Leftarrow
|-
| <amsmath>\leftarrow</amsmath>
| \leftarrow
|-
| <amsmath>\Leftrightarrow</amsmath>
| \Leftrightarrow
|-
| <amsmath>\vec{x}</amsmath>
| \vec{x}
|-
| <amsmath>{n \choose k}</amsmath>
| {n \choose k}
|-
| <amsmath>\Box</amsmath>
| \Box
|-
| <amsmath>\forall</amsmath>
| \forall
|-
| <amsmath>\exists</amsmath>
| \exists
|-
| <amsmath>\in</amsmath>
| \in
|-
| <amsmath>\not\in</amsmath>
| \not\in
|-
| <amsmath>\mbox{Taylor}   f(x) = \sum_{k=0}^{\infty } \frac{
|f^{k} (a) }{ k! } (x - a)^k</amsmath>
| \mbox{Taylor}  f(x) = \sum_{k=0}^{\infty } \frac{ f^{k} (a) }{ k! } (x - a)^k
|-
| <amsmath>\mbox{Euler}^1 e^{i \varphi } := \cos \varphi + i
|\sin \varphi</amsmath>
| \mbox{Euler}^1  e^{i \varphi } := \cos \varphi + i \sin \varphi
 
|}

Latest revision as of 17:01, 30 October 2008

<amsmath>\frac{x}{y}</amsmath> \frac{x}{y}
<amsmath>\sum_{x=1}^{n}</amsmath> \sum_{x=1}^{n}
<amsmath>\prod^{x=1}_{n}</amsmath> \prod^{x=1}_{n}
<amsmath>\int_{a}^{b} f (x)\,dx</amsmath> \int_{a}^{b} f (x)\,dx
<amsmath>\frac{\partial x}{\partial y}</amsmath> \frac{\partial x}{\partial y}
<amsmath>\sqrt{x}</amsmath> \sqrt{x}
<amsmath>\sqrt[3]{x}</amsmath> \sqrt[3]{x}
<amsmath>f(x)</amsmath> f(x)
<amsmath>\lim_{x\to\infty}</amsmath> \lim_{x\to\infty}
<amsmath>\sin (x)</amsmath> \sin (x)
<amsmath>\cos (x)</amsmath> \cos (x)
<amsmath>\tan (x)</amsmath> \tan (x)
<amsmath>\log (x)</amsmath> \log (x)
<amsmath>\ln (x)</amsmath> \ln (x)
<amsmath>\le</amsmath> \le
<amsmath>\ge</amsmath> \ge
<amsmath>\neq</amsmath> \neq
<amsmath>\approx</amsmath> \approx
<amsmath>\equiv</amsmath> \equiv
<amsmath>\propto</amsmath> \propto
<amsmath>\infty</amsmath> \infty
<amsmath>\alpha</amsmath> \alpha
<amsmath>\beta</amsmath> \beta
<amsmath>\gamma</amsmath> \gamma
<amsmath>\delta</amsmath> \delta
<amsmath>\epsilon</amsmath> \epsilon
<amsmath>\zeta</amsmath> \zeta
<amsmath>\eta</amsmath> \eta
<amsmath>\theta</amsmath> \theta
<amsmath>\vartheta</amsmath> \vartheta
<amsmath>\kappa</amsmath> \kappa
<amsmath>\lambda</amsmath> \lambda
<amsmath>\mu</amsmath> \mu
<amsmath>\xi</amsmath> \xi
<amsmath>\pi</amsmath> \pi
<amsmath>\rho</amsmath> \rho
<amsmath>\sigma</amsmath> \sigma
<amsmath>\tau</amsmath> \tau
<amsmath>\phi</amsmath> \phi
<amsmath>\varphi</amsmath> \varphi
<amsmath>\chi</amsmath> \chi
<amsmath>\psi</amsmath> \psi
<amsmath>\omega</amsmath> \omega
<amsmath>\Rightarrow</amsmath> \Rightarrow
<amsmath>\rightarrow</amsmath> \rightarrow
<amsmath>\Leftarrow</amsmath> \Leftarrow
<amsmath>\leftarrow</amsmath> \leftarrow
<amsmath>\Leftrightarrow</amsmath> \Leftrightarrow
<amsmath>\vec{x}</amsmath> \vec{x}
<amsmath>{n \choose k}</amsmath> {n \choose k}
<amsmath>\Box</amsmath> \Box
<amsmath>\forall</amsmath> \forall
<amsmath>\exists</amsmath> \exists
<amsmath>\in</amsmath> \in
<amsmath>\not\in</amsmath> \not\in
<amsmath>\mbox{Taylor} f(x) = \sum_{k=0}^{\infty } \frac{ f^{k} (a) }{ k! } (x - a)^k</amsmath> \mbox{Taylor} f(x) = \sum_{k=0}^{\infty } \frac{ f^{k} (a) }{ k! } (x - a)^k
<amsmath>\mbox{Euler}^1 e^{i \varphi } := \cos \varphi + i \sin \varphi</amsmath> \mbox{Euler}^1 e^{i \varphi } := \cos \varphi + i \sin \varphi